Marital fidelity and congregation of Indian sarus crane, Grus antigone antigone in and around Alwara lake of district Kaushambi (Uttar Pradesh), India - Prakash, Shri; Verma, Ashok Kumar (International Journal of Biological Research, 2016)
Sarus crane is a monogamous bird and well known as an eternal symbol of unconditional love, devotion and good fortune. Its occurrence represents a healthy wetland ecosystem. These cranes are large, long-legged and long-necked birds belonging to family: Gruidae, order: Gruiformes, class: Aves and phylum: Chordata. Indian Sarus Crane, Grus antigone antigone is the largest of the crane species found in India. These water birds prefer open habitat like marsh areas, abundantly irrigated paddy fields, grass land and river banks as these areas suit them for foraging, roosting and nesting. It has been showing an increasing population trends in this wetland because its habitat is well suited for its population growth. The present study concerns the survey of Indian Sarus Crane in and around Alwara Lake of District Kaushambi (U.P.) during 2014 with special reference to marital fidelity and congregation. The authors reported a congregation of maximum up to 155 cranes during the study period.